Marine lebensspuren: improving the classification of seafloor traces from underwater imagery and observations - Olmo Miguez-Salas; Rachel Przeslawski; Francisco J. Rodríguez-Tovar; Alfred Uchman; Brian J. Bett; Jennifer M. Durden; Torben Riehl (Frontiers in Marine Science, 2024)
Taxonomy is a dynamic and evolving scientific field in biological and paleontological research, which describes and systematises species and other taxa and thus lays the foundation to solve and structure biological questions. The study of past (fossil) and modern (present) seafloor traces holds huge potential for understanding the composition, behavioural ecology, and ecosystem impact of benthic communities, e.g., in terms of bioturbation and carbon cycling. In trace fossil research (paleoichnology), ichnotaxonomical analysis is based on the application of ichnotaxobases, morphology being the most important and useful criterion. However, marine neoichnological analyses (modern traces; lebensspuren) have no standardised ichnotaxobases. In the literature, classification based on morphological descriptions or behavioural assignations can be found, but without consensus. This lack of standardised terminology hinders comparisons among studies and regions. Through this manuscript, we discuss the limitations of marine lebensspuren characterisation through underwater observations and how further classification could be done (i.e., possible ichnotaxobases). Considering that most of the classifications will be based on marine still images, we propose a classification for marine lebensspuren based on a combination of three labels: 1) morphology (e.g., M-ridged trail), 2) behaviour determination (e.g., locomotion and feeding), and 3) tracemaker taxonomy (e.g., Echinocrepis rostrata ). Accordingly, the classification will be 1) M-ridged trail 2) Locomotion and feeding 3) Echinocrepsis rostrata . A set of recommendations is given to address all three labels. Also, we describe some of the contrasting positions of paleo- and neoichnology, particularly where a solution presently seems difficult to find, and argue that open nomenclature could be useful as still images contain large amounts of information. Finally, we provide examples of the usage of this classification for input to a marine lebensspuren online repository and how this nomenclature can help to compare worldwide lebensspuren in a consistent way.